Pre-Service Teacher Students’ Perception towards Speaking English - Rofi'i, Agus; Nurhidayat, Eka (Journal of English Language Learning, 2019)
Language is a communication tool to convey ideas or opinions and feelings to others. Through language, people can be interconnected, share, learn from each other, and improve their intellectual abilities. The ability to communicate in English is very crucial in the world of work. One of the abilities demanded by alumni of English education study programs is the ability to communicate in English. So far, based on the experience of researchers while teaching, there are still students who are unable to speak in public or make English presentations. They have less confidence to do it. The fourth-semester students of the English Education Study Program applied This English Presentation method. This research uses descriptive qualitative method to describe in public speaking by using English